Wintering Characteristics Of Coccinellids - Sh.Q. Yuldasheva; M.Murotova (Zien Journals, 2024)
Among predatory entomophages, representatives of the Coccinellid family play an important role in effectively eliminating most pests of agricultural crops
Keywords: Coccinellid family; agricultural crops; biological control